The Influence Of Product Quality And Customer Experience Against Buying Decision (Survey On Consumers Of Rabbani Tasikmalaya) - Nira Dya Dara; Budhi Wahyu Fitriadi; Barin Barlian (Penerbit Jurnal Indonesia, 2023)
The purpose of this study is to determine the effect of product quality and customer experience on the buying decision to the Rabbani Tasikmalaya.The research method used is a questionnaire method with a survey approach of 100 respondents who are consumers of Rabbani. The types of data used are primary data and secondary data. The data analysis technique used is multiple regression analysis. The results of this test prove that product quality and customer experience have a significant effect both partially and simultaneously on the buying decision consumers Rabbani Tasikmalaya.